2015
DOI: 10.1186/s12933-015-0178-3
|View full text |Cite
|
Sign up to set email alerts
|

The association of the treatment with glucagon-like peptide-1 receptor agonist exenatide or insulin with cardiovascular outcomes in patients with type 2 diabetes: a retrospective observational study

Abstract: BackgroundTo evaluate the association of treatment with glucagon-like peptide-1 (GLP-1) receptor agonist exenatide and/or insulin on macrovascular outcomes in patients with type 2 diabetes (T2DM).MethodsWe conducted a retrospective longitudinal pharmaco-epidemiological study using large ambulatory care data to evaluate the risks of heart failure (HF), myocardial infarction (MI) and stroke in established T2DM patients who received a first prescription of exenatide twice daily (EBID) or insulin between June 2005… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(73 citation statements)
references
References 35 publications
4
69
0
Order By: Relevance
“…Furthermore, in randomized trials, EQW has been reported to provide improved glycaemic control compared with EBID . In a retrospective study, exenatide was associated with a reduced cardiovascular risk compared with insulin …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in randomized trials, EQW has been reported to provide improved glycaemic control compared with EBID . In a retrospective study, exenatide was associated with a reduced cardiovascular risk compared with insulin …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, treatment duration estimates from the "continuous" approach are more sensible to the set of selected medications. The difference between methods is particularly prominent in studies involving multiple drugs as opposed to single drug therapies or focusing on the order of treatment initiation [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…Such real-world analysis provides an extremely valuable means for the understanding of drug utilization patterns, treatment initiation periods following the diagnosis of a disease, the effectiveness of specific therapies on disease-related risk factors, and possible associations of therapies with long-term outcomes [1,6]. These studies warrant appropriate extraction of longitudinal information on prescriptions or medications at individual patient level, inappropriate extraction of the data may result in misleading inferences reported [33 -35].…”
Section: Introductionmentioning
confidence: 99%
“…Further, in diabetic patients, GLP‐1 agonists and DPP4 inhibitors both reduce the risk of heart failure, stroke and MI (Paul et al . , Velez et al . ).…”
Section: Direct Effects Of Glp‐1 On the Cardiovascular Systemmentioning
confidence: 99%